The Effect of Sharia Financial Literacy, Perceived Usefulness, Perceived Ease of Use on Online Waqf Decisions - Muhamad Nahid; Nihayatul Maskuroh; Wazin Wazin (Ekonomi, Keuangan, Investasi dan Syariah (EKUITAS), 2023)
The potential for cash waqf in Indonesia is very large, but until now the collection of waqf funds is still not optimal. Online waqf in Indonesia is an alternative solution to this potential demand. Online waqf has its own challenges. Therefore, it is important for stakeholders such as nadzirs and the government to know the factors that influence people's interest in waqf. This study uses the Structural Equation Modeling (SEM) method with the subject of wakif studies in the Banten region. Then, the research sample was taken based on the accidental sampling technique. Data analysis was carried out with SmartPLS 3.0 software by analyzing the outer and inner models. This study found that the Islamic financial literacy variable and the perceived usefulness variable had no significant effect on trust with a t-count of 0.968 ≤ t-table 1.65, p-value 0.334 ≥ 0.1. Then, the trust variable has a positive and significant effect on the cash waqf decision variable with t-count 10.629 ≥ t-table 1.65, p-value 0.000 ≤ 0.1. This study found that the Islamic financial literacy and the perceived usefulness variable also has no significant effect on trust. Then the trust variable also has a positive and significant effect on the cash waqf decision variable. The results of this study found that the variables that have the greatest influence on endogenous variables (decisions) are trust compared to Islamic financial literacy, perceived benefits, and perceived ease of use. These results can be seen in the calculation of β the biggest trust variable followed by other variables, namely Islamic financial fraud on perceived benefits, and Islamic financial fraud on perceived ease of use. The results of this research can be used as input and add new perspectives for waqf management institutions that have online platforms.